Avaliação da eficácia dos modelos de asset liability management e liability driven investment para um fundo de pensão brasileiro - Sabrina Amelia de Lima e Silva (2015)
Brazilian pension funds assume notable relevance in financial market, so that its assets reached 669 billion reais in december 2013 or 13.8% of Brazilian Gross Domestic Product. The economic environment of recent years has brought challenges in management of assets and liabilities, with emphasis being placed on the gradual decline behavior of interest rates in economy. Namely, this macroeconomic variable is one that most affects the financial and actuarial results of benefit plans. The purpose of this study is to evaluate the effectiveness of Asset Liability Management (ALM) and Liability Driven Investment (LDI) in a pension fund through Tracking Error measure. To do this, the actuarial valuation was carried out to ascertain the liabilities and the corresponding mathematical reserve of the plan, the projection of economic scenarios to model the returns of segments of investments, application of stochastic multiperiod programming in development of ALM and the adoption of correspondence between investments return rate and actuarial target oriented to the liability as a model of LDI. The effectiveness evaluation based on Tracking Error showed that the LDI model is closer to reality, revealing its relevance especially in scenarios where the focus is on the actuarial liability. However, the ALM model also had its effectiveness assured, generating even surplus results.